Efficacy of nano- and microemulsion-based topical gels in delivery of ibuprofen: an in vivo study. (17th February 2017) - Azizi, Mosayeb; Esmaeili, Fariba; Partoazar, Alireza; Ejtemaei Mehr, Shahram; Amani, Amir
Abstract: Aim: Nanoemulsion has shown many advantages in drug delivery systems. In this study, for the first time, analgesic and anti-inflammatory properties of a nanomelusion of almond oil with and without ibuprofen was compared with corresponding microemulsion and commercial topical gel of the drug using formalin and carrageenan tests, respectively. Method: Almond oil (oil phase) was mixed with Tween 80 and Span 80 (surfactants), and ethanol (co-surfactant) and them distilled water (aqueous phase) was then added to the mixture at once. Prepared nanoemulsions were pre-emulsified into a 100 ml beaker using magnet/stirrer (1000 rpm). Then, using a probe ultrasonicator (Hielscher UP400s, Hielscher, Ringwood, NJ) the nanoemulsions were formed. Results: The optimised nanoemulsion formulation containing 2.5% ibuprofen, showed improved analgesic and anti-inflammatory effects compared with commercial product and corresponding microemulsion product containing 5% ibuprofen (i.e. twice the content of ibuprofen in the nanoemulsion) in vivo . The nanoemulsion preparation showed superior analgesic activities during chronic phase. Also, it decreased the inflammation from the first hour, while the microemulsion and the commercial product started to show their anti-inflammatory effects after 2 and 3 h, respectively. Conclusion: Our finding suggests that the size of the emulsion particles must be considered as an important factor in topical drug delivery systems.